Electrostatic interactions mediate the nucleation and growth of a bacterial functional amyloid - Bhoite, Sujeet S.; Kolli, Divya; Gomulinski, Mark A.; Chapman, Matthew R. (Frontiers in Molecular Biosciences, 2023)
Bacterial biofilm formation can have severe impacts on human and environmental health. Enteric bacteria produce functional amyloid fibers called curli that aid in biofilm formation and host colonization. CsgA is the major proteinaceous component of curli amyloid fibers and is conserved in many gram-negative enteric bacteria. The CsgA amyloid core consists of five imperfect repeats (R1-R5). R2, R3, and R4 have aspartic acid (D) and glycine (G) residues that serve as “gatekeeper” residues by modulating the intrinsic aggregation propensity of CsgA. Here, using mutagenesis, salt-mediated charge screening, and by varying pH conditions, we show that the ability of CsgA variants to nucleate and form amyloid fibers is dictated by the charge state of the gatekeeper residues. We report that in Citrobacter youngae CsgA, certain arginine (R) and lysine (K) residues also act as gatekeeper residues. A mechanism of gatekeeping is proposed wherein R and K residues electrostatically interact with negatively charged D residues, tempering CsgA fiber formation.